Nafion and Multiwall Carbon Nanotube Modified Ultrananocrystalline Diamond Microelectrodes for Detection of Dopamine and Serotonin - An-Yi Chang; Shabnam Siddiqui; Prabhu U. Arumugam (Micromachines, 2021)
Neurochemicals play a critical role in the function of the human brain in healthy and diseased states. Here, we have investigated three types of microelectrodes, namely boron-doped ultrananocrystalline diamond (BDUNCD), nafion-modified BDUNCD, and nafion–multi-walled carbon nanotube (MWCNT)-modified BDUNCD microelectrodes for long-term neurochemical detection. A ~50 nm-thick nafion–200-nm-thick MWCNT-modified BDUNCD microelectrode provided an excellent combination of sensitivity and selectivity for the detection of dopamine (DA; 6.75 μA μM−1 cm−2) and serotonin (5-HT; 4.55 μA μM−1 cm−2) in the presence of excess amounts of ascorbic acid (AA), the most common interferent. Surface stability studies employing droplet-based microfluidics demonstrate rapid response time (<2 s) and low limits of detection (5.4 ± 0.40 nM). Furthermore, we observed distinguishable DA and 5-HT current peaks in a ternary mixture during long-term stability studies (up to 9 h) with nafion–MWCNT-modified BDUNCD microelectrodes. Reduced fouling on the modified BDUNCD microelectrode surface offers significant advantages for their use in long-term neurochemical detection as compared to those of prior-art microelectrodes.